2014
DOI: 10.1016/j.egypro.2014.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Heat Transfer and Friction Factor of Silver Nanofliud in Absorber/Receiver of Parabolic Trough Collector with Twisted Tape Inserts

Abstract: Comparative study on performance of different twisted tape inserts in the absorber tube of parabolic trough collector (PTC) are presented in this paper. The heat transfer equations for fully developed flow under quasi-steady state conditions have been developed in order to analyze the thermal characteristics and effect of operating parameters on system performance. The numerical simulations have been employed for five different twisted tape inserts with mass flow rate ranging from 0.06 kg/s to 0.16 kg/s. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…The correlation for Nu and lie in the range of ± 4 % and ± 7 % respectively. Similar studies were performed by Song et al [5], Waghole et al [6], Ghadirijafarbeigloo et al [7] and Zhu et al [8].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The correlation for Nu and lie in the range of ± 4 % and ± 7 % respectively. Similar studies were performed by Song et al [5], Waghole et al [6], Ghadirijafarbeigloo et al [7] and Zhu et al [8].…”
Section: Introductionsupporting
confidence: 72%
“…In equation (6), Uo can be raised by increasing hfi as rest all parameters (except UL) remains unchanged. However, UL is inversely proportional to hf i.…”
Section: Heat Transfer Augmentation In Ptcmentioning
confidence: 99%
“…They showed that nanofluids have excellent potential for power tower applications with 5 to 10% improvement in efficiency. Waghole et al [24] experimentally investigated the heat transfer and friction factor of silver nanofluids in the absorber/receiver of a parabolic trough receiver with twisted tape inserts. Recently, Sokhansefat et al [25] investigated heat transfer enhancement in a parabolic trough collector tube using a synthetic oil-Al 2 O 3 nanofluid for the nanoparticle concentration less than 5% and operating temperatures of 300 K, 400 K and 500 K. They showed that the heat transfer performance increases as the volumetric concentration of nanoparticles increases.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency was shown to increase between 5 and 10% with the use of 7 nanofluids. Waghole et al [35] experimentally investigated the performance of a parabolic trough system with silver nanofluids in the absorber/receiver with twisted tape inserts.…”
mentioning
confidence: 99%